From benchmarking to global leadership: Singapore’s health sciences authority’s journey to WHO maturity level 4 and WHO-Listed Authority status for medicines - Dorothy Toh; Adena Lim; Agnes Chan; Alvin Chia; Pei San Ang; Annie Tan; Belinda Foo; Betty Chan; Limei Chong; Qiuyi Choo; Chih Tzer Choong; Christine Ho; et al. (Frontiers in Medicine, 2026)
This article aims to describe Singapore Health Sciences Authority’s (HSA’s) multi-year journey to attaining World Health Organisation (WHO) Maturity Level 4 (ML4) and WHO-Listed Authority (WLA) status for medicines regulatory functions, presenting HSA as a descriptive policy case study on the practical application of the WHO Global Benchmarking Tool (GBT) and WLA frameworks. It outlines the benchmarking and Performance Evaluation (PE) processes, including the scope of assessment, phased reviews, and key milestones achieved between 2021 and 2024. HSA became the first regulator globally to achieve ML4 for medicines, before progressing through the WLA Performance Evaluation and eventually securing WLA listing across all medicines’ regulatory functions. The article examines the institutional factors that enabled these achievements, including strong governance, sustained leadership commitment, technical expertise, digitalised regulatory workflows, and close engagement with international partners. The findings highlight that ML4 and WLA recognition are not merely markers of national regulatory excellence, but strategic enablers that strengthen regulatory credibility, support international reliance by other authorities, and contribute to more timely access to safe, effective, and quality-assured health products. HSA’s experience also underscores that attaining and sustaining advanced regulatory maturity requires long-term investment in systems, people, oversight, and innovation, particularly as regulatory agencies take on broader roles in supporting regional and global public health.